How Does Competition Impact Bank Risk-Taking in Dual-Banking System in Emerging Market - Tan, Dyi Ting (2015)
This paper studies and compares competition and risk-taking behaviours within the two banking systems consisting of 59 Islamic banks and 149 conventional banks from 10 emerging countries between 2006 and 2013. The level of competitiveness between the two types of banks is determined using Lerner index and estimations show that Islamic banks have lower market power than conventional banks. After controlling all the bank and country-specific variables, the results show that competition and risk are negatively related for conventional banks and inversely related for Islamic banks which undoubtedly emphasize that inherent difference between risk-competition relationships among these two distinct bank types. However, the results also give a clear evidence of a significant and positive risk-competition relationship for all banks. Overall, the results provide evidence in favour of traditional view where higher monopoly market power associated with less competition reduces the banks’ risk-taking behaviours.